3D printing of alginate dialdehyde-gelatin (ADA-GEL) hydrogels incorporating phytotherapeutic icariin loaded mesoporous SiO2-CaO nanoparticles for bone tissue engineering - Monavari, Mahshid; Homaeigohar, Shahin; Fuentes Chandia, Miguel Angel; Nawaz, Qaisar; Monavari, Mehran; Venkatraman, Arvind; Boccaccini, Aldo R. (Materials Science and Engineering C, 2021)
3D printing enables a better control over the microstructure of bone restoring constructs, addresses the challenges seen in the preparation of patient-specific bone scaffolds, and overcomes the bottlenecks that can appear in delivering drugs/growth factors promoting bone regeneration. Here, 3D printing is employed for the fabrication of an osteogenic construct made of hydrogel nanocomposites. Alginate dialdehyde-gelatin (ADA-GEL) hydrogel is reinforced by the incorporation of bioactive glass nanoparticles, i.e. mesoporous silica-calcia nanoparticles (MSNs), in two types of drug (icariin) loading. The composites hydrogel is printed as superhydrated composite constructs in a grid structure. The MSNs not only improve the mechanical stiffness of the constructs but also induce formation of an apatite layer when the construct is immersed in simulated body fluid (SBF), thereby promoting cell adhesion and proliferation. The nanocomposite constructs can hold and deliver icariin efficiently, regardless of its incorporation mode, either as loaded into the MSNs or freely distributed within the hydrogel. Biocompatibility tests showed that the hydrogel nanocomposites assure enhanced osteoblast proliferation, adhesion, and differentiation. Such optimum biological properties stem from the superior biocompatibility of ADA-GEL, the bioactivity of the MSNs, and the supportive effect of icariin in relation to cell proliferation and differentiation. Taken together, given the achieved structural and biological properties and effective drug delivery capability, the hydrogel nanocomposites show promising potential for bone tissue engineering.
CRIS-Team Scopus Importer:2021-10-29
Keywords: 3D printed hydrogel; ADA-GEL; Bone tissue engineering; Drug delivery; Mesoporous SiO; Phytotherapeutic agent